2020
DOI: 10.3390/nu12092655
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B1 Intake in Multiple Sclerosis Patients and its Impact on Depression Presence: A Pilot Study

Abstract: Vitamin B1, or thiamine, is one of the most relevant vitamins in obtaining energy for the nervous system. Thiamine deficiency or lack of activity causes neurological manifestations, especially symptoms of depression, intrinsic to multiple sclerosis (MS) and related to its pathogenesis. On this basis, the aim of this study was to determine the possible relationship between the nutritional habits of patients with MS and the presence of depression. Therefore, a cross-sectional and observational descriptive study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Additionally, thiamine (vitamin B1) deficiency was described to induce neurologic manifestations in PwMS, mainly related with depressive behavior. 49 Finally, we acknowledge the limitations of using fetal bovine serum (FBS) during the astrocyte differentiation protocol, even in low concentrations, as it impacts mainly the inflammatory phenotype of these cells over time, as previously published. 31 Although several studies have used FBS to differentiate astrocytes from iPSCs, aiming to minimize the formation of neurons, 10,50 future studies focusing on astrocyte responses to inflammation using iPSC-based models of MS should consider the possibility of using serum-free differentiation protocols to reduce this bias and resemble in vivo models.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Additionally, thiamine (vitamin B1) deficiency was described to induce neurologic manifestations in PwMS, mainly related with depressive behavior. 49 Finally, we acknowledge the limitations of using fetal bovine serum (FBS) during the astrocyte differentiation protocol, even in low concentrations, as it impacts mainly the inflammatory phenotype of these cells over time, as previously published. 31 Although several studies have used FBS to differentiate astrocytes from iPSCs, aiming to minimize the formation of neurons, 10,50 future studies focusing on astrocyte responses to inflammation using iPSC-based models of MS should consider the possibility of using serum-free differentiation protocols to reduce this bias and resemble in vivo models.…”
Section: Discussionmentioning
confidence: 89%
“…Beyond its canonical role in inhibiting lymphocyte trafficking to the CNS, this drug induced an anti‐inflammatory phenotype in human astrocytes, 48 suggesting that part of the effects of fingolimod may rely on the modulation of astrocyte functions in PwMS, which should be further investigated. Additionally, thiamine (vitamin B1) deficiency was described to induce neurologic manifestations in PwMS, mainly related with depressive behavior 49 …”
Section: Discussionmentioning
confidence: 99%
“…Specifically in MS, sphingosine-1-phosphate receptor is a therapeutic target of the widely used medication fingolimod, which is approved for the treatment of PwMS, and it has been demonstrated that beyond its canonical role in inhibiting lymphocyte trafficking to the CNS, this drug induced an antiinflammatory phenotype in human astrocytes 41 , suggesting that part of the effects of fingolimod may rely on the modulation of astrocyte functions in PwMS, which should be further investigated. Additionally, thiamine (vitamin B1) deficiency was described to induce neurologic manifestations in PwMS, mainly related with depressive behavior 42 .…”
Section: Discussionmentioning
confidence: 99%
“…In one of the pilot studies on vitamin B 1 consumption in patients with multiple sclerosis, patients who consumed fewer total carbohydrates and mainly simple carbohydrates showed a higher level of depression, which is characteristic of MS [ 47 ]. A lower total carbohydrate intake than recommended can interfere with vitamin B 1 activity because its function is to metabolize carbohydrates to obtain glucose as a source of neuronal energy [ 48 ].…”
Section: Carbohydratesmentioning
confidence: 99%
“…Deficiency or lack of thiamine activity (vitamin B 1 ) causes neurological symptoms, especially symptoms of depression, inherent in multiple sclerosis and related to its pathogenesis. In a pilot study by Orti et al ., a significant negative correlation was found between depression and thiamine consumption [ 47 ]. The dietary intake associated with thiamine activity in the MS patient population exhibits an imbalance characterized by a lower recommended total carbohydrate intake, which consists mainly of simple carbohydrates.…”
Section: Vitaminsmentioning
confidence: 99%